UJI TANJAK MOBIL LISTRIK BLACK BULL POLITEKNIK HARAPAN BERSAMA - Haqiqi, Ziyadil Achyar (Politeknik Harapan Bersama Tegal, 2023)
The development of transportation facilities is always evolving along with the progress of the times, one of which is vehicles using electric power as the main driving force. Electric cars are environmentally friendly vehicles and are expected to be able to significantly reduce the use of petroleum or ancient fossil fuels. Some of the advantages of electric cars compared to liquid fuel cars are that they sound smooth, have no smell and are free from smoke. He added that electric cars are seen as cars of the future. The purpose of this research is to determine the Hill Test of the Black Bull Electric Car at Harapan Bersama Polytechnic. The method used is varying the angle of inclination for climbing power, namely 10 degrees, 15 degrees and 20 degrees. The results of this research were at a slope angle of 10 degrees and a distance of 10 meters with an average initial battery capacity of 77.4 volts to an average final battery capacity of 77.1 volts with an average speed of 19 km/hour in 1.93 seconds. . Testing with an inclination angle of 15 degrees with an average initial battery capacity of 78.5 volts to an average final battery capacity of 78.3 volts with an average speed of 23 km/hour in 3.40 seconds. Test results with an inclination angle of 20 degrees with an average initial battery capacity of 77.2 volts to an average final battery capacity of 77 volts at a speed of 28 km/hour in 2.62 seconds.